PEMBELAJARAN INSTRUKSIONAL TERPROGRAM DALAM PENINGKATAN EFEKTIVITAS PEMBELAJARAN GAMBAR TEKNIK - Subiyono, Subiyono (Jurnal Cakrawala Pendidikan, 2010)
Abstract This study aimed to find empirical evidence that in Technical Drawing students taught by the programmed instruction model attained higher achievement than those taught by the conventional teaching model. This study was a quasiexperimental study. The research subjects were students of the Department of Mechanical Engineering, the Faculty of Engineering, the Yogyakarta State University. Group A2 was selected as the experimental group, consisting of regular S1 students, and Group B1 as the control group, consisting of regular D3 students. The group members were non-randomly selected. The data were analyzed using the t-test. The result showed that the tobserved (17.717) was higher than the ttable (2.038) at p < .05, indicating that there was a significant difference between the two groups. The students in the experimental group attained a higher mean score than those in the control group. In other words, in Technical Drawing, the students taught by the programmed instruction model attained higher achievement than those taught by the conventional teaching method. Keywords: programmed instruction, Technical Drawing